Canon and Archive: Yahwism in Elephantine and Al-Yā?ūdu as a Challenge to the Canonical History of Judean Religion in the Persian Period - Granerød, Gard (Journal of Biblical literature, 2019)
This article offers a methodological and factual discussion of Judean religion in the Persian period. Its theoretical framework is influenced by Aleida Assmann's works on canon and archive from the perspective of cultural memory, especially the notion that there can be an exchange between the passive memory ("the archive") and the actively circulated memory ("the canon"). I argue that the "canonized narrative" should be challenged by sources from historical archives, namely, the Elephantine documents and the recently published Al-Yā?ūdu documents. I contend further that we probably get closer to a historically verifiable Persian-period Judean religion in the Elephantine documents than in the world of the thoroughly edited texts of the Hebrew Bible. Moreover, even though the Al-Yā?ūdu documents are not as informative as the Elephantine documents, they nevertheless convey vague traces of practiced Judean religion. I conclude with five propositions as to how the documents from Elephantine and Al-Yā?ūdu can and should modify and adjust the canonized image of what Judean religion actually looked like in the Persian period.